E-learning and its impact on the quality of higher education in Iraq: A survey study to faculty members in Baghdad and AlMustansiriya universities - AL-Tabtabai, Ali Ahmed Ameen; Asadi, Mansoor (Al-Adab Journal, 2022)
This study aimed to identify the reality of e-learning in general, and especially in Iraqi universities, and the extent of its impact on the quality of higher education, and to show that from the point of view of the faculty members as the main supporter of the educational process and those who maintain its sobriety, so a questionnaire was prepared for them and distributed randomly to the selected sample. In addition to recording notes about it The current research was limited to a sample of (313) professors of Iraqi universities in the province of Baghdad (University of Baghdad) as the mother university and (Al-Mustansiriya University) The researcher took the survey method, one of the types of descriptive analysis method as a design for the research, and the research community consisted of university professors within the borders of the geographical area of ​​the province of Baghdad, and the universities of Baghdad and Al-Mustansiriya were chosen to represent the sample of the current study. Teaching, and general evidence for teachers about e-learning, the pros and cons of e-learning, in addition to the obstacles of e-learning. The questionnaire’s paragraphs were statistically analyzed, and the questionnaire procedures took nearly two months, and the researcher analyzed the results he reached using the t-test, to verify the hypothesis Research and to calculate the significance of the differences between the averages to identify the effectiveness of e-learning and its impact on the quality of higher education in Iraqi universities, and found a statistically significant difference at the level of significance (0.05), it appeared that the role of e-learning is one of the reasons for the low quality of education in Iraqi universities, by comparing Between the arithmetic average and the hypothetical average, where the role of e-learning is negatively reflected on the reality of the quality of higher education because it does not require that attention And thinking may sometimes be a unilateral connection, in light of the results of the research, the researcher concluded that e-learning in Iraq is in dire need of elements and effort in order to contribute to improving the reality of higher education in Iraqi universities, due to the weak infrastructure that prevents leaving the old ways of education.